Rapid photo-crosslinking drug sustained release type multifunctional hydrogel corneal contact lens and preparation method thereof

Through rapid photocrosslinking technology, combined with quaternized chitosan and traditional Chinese medicine ingredients, a drug-sustained multifunctional hydrogel corneal contact lens is formed, which solves the problems of complex traditional preparation processes and insufficient antibacterial performance, and achieves high efficiency and safety ophthalmic treatment effect.

CN119219847AActive Publication Date: 2024-12-31CHINA PHARM UNIV

Patent Information

Application Number
CN202411161422.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-31
Estimated Expiration
2044-08-23

Smart Images

  • Figure CN119219847A_ABST
    Figure CN119219847A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid photo-crosslinking drug sustained release type multifunctional hydrogel corneal contact lens and a preparation method thereof. The preparation method comprises the following steps: (1) preparing quaternized chitosan, an acrylate monomer, methacrylic acid, a crosslinking agent and an initiator into a reaction mixed solution according to a ratio; (2) transferring the reaction mixed solution into a mold, carrying out an ultraviolet irradiation free radical polymerization reaction, after the reaction is finished, demolding, taking out hydrogel, washing, and carrying out freeze drying treatment to obtain freeze-dried hydrogel; and (3) immersing the freeze-dried hydrogel into a drug monomer solution until the hydrogel is completely swelled. The corneal contact lens prepared by the method disclosed by the invention can be polymerized in one step and rapidly prepared, has proper water content of a finished product, has excellent light transmission and mechanical properties, can effectively load traditional Chinese medicine antibacterial drugs and prolong the release time of the drugs, has a remarkable curative effect in treatment of bacterial keratitis, and is suitable for popularization and application. As a therapeutic corneal contact lens, the corneal contact lens has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer hydrogels, and in particular to a fast photo-crosslinked drug sustained-release multifunctional hydrogel corneal contact lens and a preparation method thereof. Background Art

[0002] Currently, eye drops containing broad-spectrum antibiotics are commonly used in the clinical treatment of BK. However, due to the problem of drug resistance caused by the abuse of antibiotics and the limitations of traditional drug administration methods, there is an urgent need to develop more effective BK treatments.

[0003] Drug-containing contact lenses provide higher drug bioavailability and fewer side effects by maintaining a more constant and controllable drug concentration in the tear film, and have become a research hotspot in current ophthalmic treatment. When drug-containing contact lenses are worn on the eyes, most of the loaded drugs diffuse from the lens into the tear film behind the lens. Under the protection of the lens, the released drugs can prevent the blink reflex and tear exchange, have a longer residence time in front of the cornea, and have a more direct diffusion path to the ocular surface. At the same time, in order to further improve the function of corneal contact lenses, researchers have begun to focus on strategies to achieve drug loading and performance optimization by introducing other monomers. Acrylate monomers are the main materials of contact lenses on the market, but they still have some problems. For example, these materials are prone to bacterial adhesion and cannot be worn for a long time, which limits their scope of application. There is an urgent need to develop a contact lens that improves its insufficient antibacterial properties.

[0004] The side chains of acrylate monomers contain hydrophilic hydroxyl groups, which not only endow the material with good hydrophilicity, but also allow for chemical modification, providing a solid foundation for the functional modification of corneal contact lenses.

[0005] CS is a chitin-derived biopolymer with high biocompatibility, non-toxicity and good biodegradability. However, the high crystallinity and low solubility of CS limit its application in the biomedical field. To overcome these limitations, researchers have developed quaternized chitosan (QCS), which has great potential in biomedical applications due to its good water solubility, biocompatibility, biodegradability and antibacterial activity, and carries a large amount of cationic charge.

[0006] Traditional Chinese medicine ingredients have received increasing attention in the field of ophthalmology in recent years because of their safety, effectiveness, low toxicity, and lack of drug resistance compared to antibiotics. At present, there are still many gaps in the research on the application of traditional Chinese medicine ingredients in ophthalmic medical materials. For example, traditional Chinese medicine polyphenols and flavonoids have anti-inflammatory, antioxidant and antibacterial effects. At the same time, their rich active groups provide a solid foundation for the innovative modification and functionalization of ophthalmic materials.

[0007] Although the above materials have shown unique advantages in individual applications, they still face the challenges of single performance and insufficient bioavailability caused by traditional drug delivery methods, which limits their wide application in ophthalmic treatment. Due to the limitations of single materials in ophthalmic treatment, it is urgent to develop an innovative material combination strategy. By integrating the chemical plasticity of acrylate monomers, the antibacterial properties of quaternized chitosan, and the multi-target and multi-pathway therapeutic advantages of traditional Chinese medicine ingredients, a new type of ophthalmic preparation is expected to be developed. It is expected that this combination strategy will not only improve the comprehensive performance of the material, but also incorporate multiple biological activities to achieve more effective and lasting therapeutic effects. Compared with traditional eye drops of a single drug, this combination preparation will reduce the number of medications, reduce eye irritation, and improve patient compliance, thereby significantly enhancing the bioavailability of ophthalmic drugs. This innovative combination preparation is expected to fill the gap in the field of ophthalmic treatment and show great application potential and clinical value.

[0008] In addition, the preparation of traditional contact lenses often requires high temperature and long time, with low efficiency and complex process, which is not conducive to industrial production. There is an urgent need to develop a simple and efficient new preparation method. Photocrosslinking technology uses light of a specific wavelength (such as ultraviolet light or visible light) to trigger the reaction and promote the formation of stable covalent bonds between molecules. It is gradually becoming a powerful tool to solve this problem. Specifically, the photocrosslinking process involves the use of photoinitiators, which are activated under light conditions to trigger the polymerization reaction of double bonds in monomers or polymers, thereby quickly forming a stable network structure. This technology has mild reaction conditions, fast preparation speed, and excellent biocompatibility. Compared with traditional thermal polymerization crosslinking methods, the preparation process is simpler and more efficient. The application of photocrosslinking technology is expected to significantly improve the production efficiency of contact lenses, simplify the manufacturing process, and open up new possibilities for industrial-scale production. Summary of the invention

[0009] The purpose of the present invention is to provide a fast photocrosslinked drug sustained-release multifunctional hydrogel contact lens and a preparation method thereof, so as to overcome the technical problems of the complicated preparation process of traditional contact lenses, the insufficient antibacterial performance of materials, and the safety of various initiators. The drug sustained-release multifunctional hydrogel contact lens provided by the present invention can be polymerized in one step and prepared quickly, and the finished product has a suitable water content, excellent light transmittance, and excellent mechanical properties, can effectively load traditional Chinese medicine antibacterial drugs, and prolong the release time of the drugs, and shows excellent therapeutic effect in the treatment of bacterial keratitis. It has broad market application prospects as a therapeutic contact lens.

[0010] To achieve the above object, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention claims a method for preparing a fast photo-crosslinked drug sustained-release multifunctional hydrogel corneal contact lens, the preparation method comprising the following steps:

[0012] (1) adding quaternized chitosan, acrylate monomers, and methacrylic acid to water in proportion, and using ultrasound and stirring to completely dissolve the quaternized chitosan; then adding a crosslinking agent and an initiator in sequence, and using ultrasound and stirring to completely dissolve the initiator to form a reaction mixture;

[0013] (2) transferring the reaction mixture into a mold, performing a UV-light free radical polymerization reaction, and after the reaction is completed, removing the hydrogel from the mold and washing it, and freeze-drying the washed hydrogel to obtain a freeze-dried hydrogel;

[0014] (3) Immersing the freeze-dried hydrogel in a drug monomer solution until the hydrogel is completely swollen to obtain a drug sustained-release multifunctional hydrogel corneal contact lens.

[0015] Further, the contents of the components in the reaction mixture in step (1) are: 30 vol% to 80 vol% of acrylate monomers, 0.6 vol% to 2 vol% of methacrylic acid, 0.001 to 3 g / L of quaternized chitosan, 0.5 vol% to 1.6 vol% of cross-linking agent, 0.01 to 1.5 g / L of initiator, and the balance is water. Preferably, the contents of the components in the reaction mixture are: 40 vol% to 80 vol% of acrylate monomers, 0.6 vol% to 2 vol% of methacrylic acid, 0.1 to 3 g / L of quaternized chitosan, 0.5 vol% to 1.6 vol% of cross-linking agent, 0.1 to 1.5 g / L of initiator, and the balance is water. Further preferably, the contents of the components in the reaction mixture are: 50 vol% to 80 vol% acrylate monomer, 0.6 vol% to 2 vol% methacrylic acid, 0.3 to 3 g / L quaternized chitosan, 0.5 vol% to 1.6 vol% cross-linking agent, 0.5 to 1.5 g / L initiator, and the balance is water.

[0016] Furthermore, the concentration of the drug monomer solution in step (3) is 0.01 to 10 g / L. Preferably, the concentration of the drug monomer solution is 0.5 to 10 g / L.

[0017] The solvent for preparing the drug monomer solution includes but is not limited to water and PBS buffer solution.

[0018] Furthermore, the acrylic acid ester monomer is hydroxyethyl methacrylate (HEMA) or glyceryl methacrylate.

[0019] Furthermore, the drug monomer is any one or at least two of epigallocatechin gallate (EGCG), epicatechin, epigallocatechin, chlorogenic acid, gallic acid, salidroside and salvianolic acid B.

[0020] Furthermore, the crosslinking agent is ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol diacrylate, polyethylene glycol dimethacrylate or dicyclopentenyl acrylate.

[0021] Furthermore, the initiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone I2959 or 2-hydroxy-2-methyl-1-phenyl-1-propanone D1173.

[0022] Furthermore, in step (2), the wavelength of light for the ultraviolet light free radical polymerization reaction is 300-400 nm, and the light intensity is 10-1500 mW / cm 2 , polymerization time 15-40min; the demolding temperature is 70-80°C, and after demolding, the hydrogel is washed in pure water for 3-7d, and the pure water is replaced every day.

[0023] Furthermore, in step (3), the freeze-dried hydrogel is immersed in the drug monomer solution on a shaker in the dark, the immersion temperature is 15-40°C, the rotation speed is 100 rpm, and the immersion time is 24-72 hours. After the hydrogel is fully swollen and adsorbs the drug, the corneal contact lens is taken out to obtain a drug-release multifunctional hydrogel corneal contact lens.

[0024] In a second aspect, the present invention seeks to protect the fast photo-crosslinked drug sustained-release multifunctional hydrogel corneal contact lens prepared by the above method.

[0025] Compared with the prior art, the present invention has the following significant advantages:

[0026] 1. The present invention provides a method for preparing hydrogel corneal contact lenses by rapid photocrosslinking. Compared with traditional preparation, this preparation method is not affected by temperature, and the photocrosslinking molding is carried out in one step, and the process is simple and easy to operate.

[0027] 2. The drug-release multifunctional hydrogel contact lens prepared by the present invention can be combined with the modified biomacromolecule material quaternized chitosan, thereby improving the performance disadvantages of traditional contact lenses and enhancing the basic physical and chemical properties of the contact lenses.

[0028] 3. The drug-release multifunctional hydrogel corneal contact lens prepared by the present invention cross-links the active ingredients of traditional Chinese medicine in a physical manner. Compared with traditional antibiotic drugs, it is safer and has no drug resistance. At the same time, the antibacterial ingredients of traditional Chinese medicine can be continuously released in a sustained-release manner, which significantly improves the bioavailability of ophthalmic drugs and has broad application prospects for the treatment of ophthalmic diseases in the future.

[0029] 4. The drug-release multifunctional hydrogel corneal contact lens prepared by the present invention can combine the advantages of each monomer component, and has multifunctional therapeutic effects such as anti-inflammatory, antioxidant, and antibacterial, providing a new solution for the clinical treatment of bacterial keratitis. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a comparison chart of infrared spectra of the hydrogel contact lenses in Examples 1-5;

[0031] Figure 2 This is a comparison chart of the water content of the hydrogel contact lenses of Examples 1-5;

[0032] Figure 3 This is a comparison chart of the light transmittance of the hydrogel contact lenses of Examples 1-5;

[0033] Figure 4 This is a comparison chart of the mechanical strength of the hydrogel contact lenses of Examples 1-5;

[0034] Figure 5 It is a comparison chart of the release curves of the hydrogel contact lenses of Examples 2-5;

[0035] Figure 6 This is a comparison chart of the antioxidant properties of the hydrogel contact lenses of Examples 1-5;

[0036] Figure 7 This is a comparison chart of the antibacterial performance of the hydrogel contact lenses of Examples 1-5 against Staphylococcus aureus and Escherichia coli;

[0037] Figure 8 This is a comparison of the hydrogel corneal contact lens of the preferred embodiment and the model group, the basic contact lens and the eyeball of the rat after the positive drug treatment of bacterial keratitis;

[0038] Fig. 9 This is a comparison of the immunofluorescence effects of the hydrogel corneal contact lens of the embodiment group and other groups after treating bacterial keratitis;

[0039] Fig.10 It is a quantitative comparison diagram of the average fluorescence intensity of immunofluorescence of the hydrogel corneal contact lens of the embodiment group and each group after the treatment of bacterial keratitis;

[0040] Fig.11 Comparative diagram of cytotoxicity of hydrogel contact lenses of Examples 1-5;

[0041] Fig.12 A comparison diagram of the hemolytic effects of the hydrogel contact lenses of Examples 1-5;

[0042] Fig.13Graph showing eye irritation effects of the hydrogel contact lens of the example. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further explained below through specific embodiments.

[0044] Example 1

[0045] (1) 5 mL of HEMA monomer, 100 μL of methacrylic acid and 5 mg of chitosan quaternary ammonium salt were added to 3 mL of water, and ultrasonicated and stirred at a temperature of 25°C-30°C for 5-15 min until they were completely dissolved; then 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and stirred and ultrasonicated for 5-15 min until the initiator was completely dissolved to form a reaction mixture.

[0046] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0047] (3) The freeze-dried gel was immersed in a PBS solution and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens without the Chinese medicine monomer.

[0048] Example 2

[0049] (1) 5 mL of HEMA monomer, 100 μL of methacrylic acid and 5 mg of chitosan quaternary ammonium salt were added to 3 mL of water, and the mixture was treated by ultrasound and stirring at a temperature of 25°C-30°C for 5-15 min until the chitosan quaternary ammonium salt was completely dissolved; then 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and the mixture was stirred and ultrasounded for 5-15 min until the initiator was completely dissolved to form a reaction mixture.

[0050] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0051] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 3 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with the Chinese medicine monomer.

[0052] Example 3

[0053] (1) Add 5 mL of HEMA monomer, 100 μL of methacrylic acid and 5 mg of chitosan quaternary ammonium salt into 3 mL of water, and treat with ultrasound and stirring at a temperature of 25°C-30°C for 5-15 minutes until the chitosan quaternary ammonium salt is completely dissolved; then add 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 in sequence, and stir and ultrasound for 5-15 minutes until the initiator is completely dissolved to form a reaction mixture.

[0054] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0055] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 5 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with traditional Chinese medicine monomers.

[0056] Example 4

[0057] (1) 5 mL of HEMA monomer, 100 μL of methacrylic acid and 5 mg of chitosan quaternary ammonium salt were added to 3 mL of water, and the mixture was treated by ultrasound and stirring at a temperature of 25°C-30°C for 5-15 min until the chitosan quaternary ammonium salt was completely dissolved; then 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and the mixture was stirred and ultrasounded for 5-15 min until the initiator was completely dissolved to form a reaction mixture.

[0058] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2, a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0059] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 8 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with the Chinese medicine monomer.

[0060] Example 5

[0061] (1) 5 mL of HEMA monomer, 100 μL of methacrylic acid and 5 mg of chitosan quaternary ammonium salt were added to 3 mL of water, and the mixture was treated by ultrasound and stirring for 5-15 min at a temperature of 25° C.-30° C. until the chitosan quaternary ammonium salt was completely dissolved; then 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and the mixture was stirred and ultrasounded for 5-15 min until the initiator was completely dissolved to form a reaction mixture;

[0062] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0063] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 10 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with the Chinese medicine monomer.

[0064] Example 6

[0065] (1) 6 mL of HEMA monomer, 80 μL of methacrylic acid and 10 mg of chitosan quaternary ammonium salt were added to 2.5 mL of water, and treated with ultrasound and stirring for 5-15 min at a temperature of 25° C.-30° C. until the chitosan quaternary ammonium salt was completely dissolved; then 90 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and stirred and ultrasonicated for 5-15 min until the initiator was completely dissolved to form a reaction mixture;

[0066] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0067] (3) The freeze-dried gel was immersed in a PBS solution and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens without the Chinese medicine monomer.

[0068] Example 7

[0069] (1) 6 mL of HEMA monomer, 110 μL of methacrylic acid and 15 mg of chitosan quaternary ammonium salt were added to 2.5 mL of water, and the mixture was treated by ultrasound and stirring at a temperature of 25° C. to 30° C. for 5 to 15 minutes until the chitosan quaternary ammonium salt was completely dissolved; then 60 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and the mixture was treated by stirring and ultrasound for 5 to 15 minutes until the initiator was completely dissolved to form a reaction mixture;

[0070] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0071] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 3 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with the Chinese medicine monomer.

[0072] Example 8

[0073] (1) 6 mL of HEMA monomer, 90 μL of methacrylic acid and 25 mg of chitosan quaternary ammonium salt were added to 3090 μL of water, and treated by ultrasound and stirring for 5-15 min at a temperature of 25° C.-30° C. until the chitosan quaternary ammonium salt was completely dissolved; then 80 μL of crosslinking agent ethylene glycol dimethacrylate and 10 mg of photoinitiator I2959 were added in sequence, and stirred and ultrasounded for 5-15 min until the initiator was completely dissolved to form a reaction mixture;

[0074] (2) The reaction mixture was transferred to the mold and exposed to ultraviolet light at a wavelength of 365 nm and an intensity of 1100 mW / cm 2 , a free radical polymerization reaction was carried out at a reaction temperature of 25°C for 20 minutes. After the reaction, the mold was immersed in 70°C hot water, the hydrogel was removed from the mold, and washed in pure water for 3 days, with the pure water replaced daily. The washed hydrogel was freeze-dried to obtain a freeze-dried gel.

[0075] (3) The freeze-dried gel was immersed in an aqueous solution of epigallocatechin gallate (EGCG) at a concentration of 3 g / L, and the mixture was immersed and shaken in a constant temperature incubator (37° C., 100 rpm) in the dark for 48 h until the hydrogel was completely swollen to obtain a hydrogel contact lens loaded with the Chinese medicine monomer.

[0076] The following performance tests were performed on the hydrogels of Examples 1-5.

[0077] 1. Water content test:

[0078] The prepared hydrogel corneal contact lens was cut into circular pieces of the same size (15 mm in diameter). The cut lenses were immersed in standard salt (phosphate buffered saline) water and completely swollen until the weight no longer increased. The surface moisture was absorbed by filter paper and the wet weight was recorded as Ws. Then the lenses were placed in a 60°C oven and dried for 48 hours. When the dry weight no longer changed, the dry weight of the hydrogel lens was recorded as Wd. The equilibrium water content EWC of the hydrogel was calculated using the following formula:

[0079]

[0080] 2. Light transmittance test:

[0081] The transmittance of the swollen sample was measured by using an ultraviolet-visible spectrophotometer within a wavelength range of 380 to 780 nm, with pure water as a control and a wavelength interval of 1 nm to obtain the transmittance at different wavelengths.

[0082] 3. Mechanical strength test:

[0083] Dumbbell-shaped hydrogel samples were prepared (test length was 16 mm, test width was 4 mm, tail width was 8.5 mm, and thickness was 1 mm). The prepared hydrogel contact lenses in different groups were immersed in physiological saline for 48 h (complete swelling). The surface moisture was absorbed by dust-free filter paper, and the tensile strength of the swollen hydrogel samples was measured using an electronic universal testing machine. The tensile rate was 50 mm / min, and the tensile properties of the hydrogel were tested.

[0084] 4. Drug loading and release kinetics:

[0085] The mass of the dry hydrogel after freeze-drying is weighed as m1. The dry hydrogel is placed in a 50mL centrifuge tube, and a volume of V0 = 5mL is added, and the concentration C0 is 3, 5, 8, and 10g / L of the drug solution (EGCG aqueous solution). Subsequently, the centrifuge tube is placed in a constant temperature incubator shaker (37°C, 100rpm) and immersed in the dark for shaking treatment. After swelling is complete, freeze-dry and weigh the weight recorded as m2. The calculation of drug loading rate of different groups of contact lenses is shown as follows:

[0086]

[0087] After soaking, wipe the drug solution on the surface of the sample with dust-free paper and put it into a 50mL centrifuge tube, and add V1 = 6mL PBS solution (0.1M, pH = 7.4). Take out V2 = 3mL of solution from the centrifuge tube at a certain time and add 3mL of fresh PBS solution. Measure the absorbance A of the solution taken out at each time point at the characteristic wavelength (274nm) and calculate the concentration C through the standard curve of the drug solution i , and calculate the cumulative release of the drug by the hydrogel, the calculation formula is as follows:

[0088]

[0089] 5. Antioxidant Determination:

[0090] Determination of the antioxidant capacity of hydrogel by DPPH method: Since the 1,1-diphenyl-2-trinitrophenylhydrazine DPPH free radical has a single electron, it can accept an electron or hydrogen ion, has maximum absorption at a wavelength of 517nm, and its alcohol solution is purple. When an antioxidant is present, due to the electron transfer mechanism, the unpaired electrons (nitrogen free radicals) in DPPH are removed, and the color of the solution fades. The degree of fading is quantitatively related to the degree of removal (i.e., the change in absorbance), so the antioxidant capacity of hydrogel corneal contact lenses can be measured by its scavenging rate of DPPH free radicals.

[0091] 10 mg of hydrogel contact lens sample was added to 30 mL of freshly prepared DPPH / ethanol solution (0.1 mM), and the mixture was kept in the dark at 37°C and 100 rpm for 20 min. DPPH was estimated by the following formula + Clearance rate.

[0092]

[0093] Wherein, Ai, Aj and Ac are the absorbance of the free radical solution mixed with the sample, the absorbance of the sample without DPPH solution and the absorbance of the DPPH free radical solution without sample at 517 nm, respectively. Each group of samples was tested 3 times and the results were averaged.

[0094] ABTS method to determine the antioxidant capacity of hydrogel: 0.2 mL of ABTS diammonium salt aqueous solution (7.4 mM) and 0.2 mL of K2S2O8 aqueous solution (2.6 mM) were mixed and reacted at room temperature in the dark for 12 h. Before use, the solution was diluted with anhydrous ethanol to an absorbance of 0.70 ± 0.02 at 752 nm. Then, 10 mg of hydrogel corneal contact lens sample was added to 30 mL of freshly prepared ABTS + The mixture was kept in the dark at 37°C and 100 rpm for 40 min. + The calculation method of free radical scavenging rate is similar to the above DPPH scavenging rate. Each group of samples was tested 3 times and the results were averaged.

[0095] 6. Antibacterial properties:

[0096] After sterilization, the sample was placed in a 12-well plate and 1 mL of a 10 6 CFU / mL of Staphylococcus aureus (Escherichia coli) bacterial solution was added to different hydrogel contact lens samples, so that the hydrogel sheets were immersed in the bacterial solution; at the same time, 1mL of bacterial solution was taken in the microwells without hydrogel as the control group; 1mL of culture medium was taken in the microwells without hydrogel as the blank group. After the inoculation, the well plate was sealed and placed in a constant temperature shaker. After incubation for 3 hours at 37°C, 100rpm, and 90% relative humidity, 200μL of each group was taken into a 96-well plate and placed in a preheated microplate reader to determine its OD value. According to the measured OD value (about 0.1), 100μL of each group was taken in 10mL of culture medium, mixed evenly, and diluted by ten-fold serial dilution method (1mL added to 9mL of culture medium). Take 100 μL of each diluted bacterial solution from different groups on a solid culture dish, use a spreader to evenly distribute the bacterial solution in the dish, seal it, and invert and culture it in a 37°C oven for 16-18 hours.

[0097] 7. Animal Experimentation

[0098] SD rats were selected for the bacterial keratitis (BK) model experiment. The experimental animals were approved by the Ethics Committee of China Pharmaceutical University and were conducted in accordance with the "Guidelines for the Care and Use of Laboratory Animals of China Pharmaceutical University". The rats were adaptively fed for one week under constant temperature and humidity conditions with no restriction on food and water.

[0099] (1) Method of establishing the BK model

[0100] Before taking any intervention steps, the ocular surface and eyeball of the rats were observed, recorded and photographed. The collection time of the recorded pictures was determined as day 0. Then, the rats were completely anesthetized by intraperitoneal injection of a newly prepared 20% urethane solution (the injection dose did not exceed 0.5 mL / 100 g). The left eye was selected as the modeling target for all groups. At the same time, the surface anesthetic proparacaine hydrochloride was instilled into one eye, and the corneal epithelial tissue of the rats was scratched with a knife. The scraped area was approximately a circle with a diameter of about 2 mm with the pupil as the center. Then 50 μL 1×10 8 CFU / mL Staphylococcus aureus (S. aureus) solution, and the eyes were closed for 24 hours. The ocular surface infection of the rats was observed using an electron upright microscope, and photos were taken and recorded as day 1. At the same time, the corneal clarity and ocular surface inflammation of the rats were scored, and the infection degree was evaluated and recorded. The scoring criteria are shown in Table 1.

[0101] Table 1 Symptom classification and scoring criteria of infectious keratitis rat model

[0102]

[0103]

[0104] (2) Experimental groups

[0105] 20 rats with similar scores were randomly divided into 4 groups. The first group of rats was used as a model control without any intervention. The second group of rats was treated by wearing pHEMA hydrogel (basic contact lens group, traditional contact lens sample), and the wearing time was no more than 8 hours a day. After each treatment, the hydrogel was taken out and ultrasonically cleaned with sterile water for repeated use on the second day. The third group was treated with antibiotics by instilling positive drug levofloxacin eye drops (levofloxacin eye drops group), and levofloxacin eye drops were used 3 times a day, 1 drop each time. The fourth group of rats was the same as the pHEMA hydrogel group process, and the hydrogel contact lens of embodiment 2 was selected for treatment (embodiment group). Afterwards, the progress of rat eyeball structure and corneal inflammation was observed every 2 days, and photographed and recorded and scored on the 3rd, 5th and 7th days respectively. The score sheet is shown in Table 1.

[0106] 8. Immunofluorescence experiment:

[0107] On the seventh day after treatment, rats in each group were euthanized. The eyeballs were removed and stored in a 20-fold volume of universal fixative for more than 24 hours to completely fix the eyeball tissue. Under a stereomicroscope, the complete rat corneal tissue was peeled off from the eyeball, and the excess conjunctiva, iris, and ciliary body tissue were removed. The corneal tissue was dehydrated overnight using an automatic dehydrator. After embedding and fixation, the corneal tissue sections in paraffin were placed in a repair box filled with citric acid antigen repair solution (pH 6.0), heated for 30 minutes, cooled naturally to room temperature, and washed with PBS three times, 5 minutes each time; then an appropriate amount of 3% bovine serum albumin blocking solution was added to evenly cover the tissue and incubated at room temperature for 30 minutes. The BSA blocking solution was shaken off, and an appropriate amount of primary antibody (IL-6, IL-1β, and TNF-α) working solution diluted in PBS was added to the tissue to evenly cover the tissue, and the sections were placed flat in a humidified box and incubated at 4°C overnight. The sections were taken out of the refrigerator the next day and rewarmed at room temperature for 30 minutes. Add appropriate amount of PBS diluted with the secondary antibody corresponding to the species of the primary antibody (Cy TM 3AffiniPure Donkey Anti-Mouse IgG(H+L) and Cy TM 3AffiniPure Donkey Anti-Rabbit IgG (H+L)), incubate at room temperature for 1 hour. Immerse the slices in autofluorescence quencher A solution, incubate at room temperature for 30 minutes, add freshly prepared DAPI working solution, and incubate at room temperature in the dark for 10 minutes. Finally, add an appropriate amount of anti-quenching sealing glue on the tissue, cover with a coverslip, and observe under a scanner. The average fluorescence intensity of each inflammatory factor was semi-quantitatively analyzed using ImageJ software (n=3).

[0108] IX. In vitro cytotoxicity assay:

[0109] After the swelling, the hydrogel contact lenses of different groups were washed three times with sterile PBS and sterilized under ultraviolet light for 4 hours (radiation wavelength 253nm). The samples and complete culture medium DMEM (Dulbecco's modified eagle medium) were added to a sterile 6-well plate at a ratio of 20mg / mL (sample / DMEM), and the 6-well plate was placed in a sterile environment at a constant temperature of 37°C. After the sample was extracted for 24 hours, the extract was taken and 10% (v / v) FBS serum and 1% (v / v) double antibody were added to make DMEM complete culture medium. After the cells were counted, they were diluted to 5×10 4 Cell suspension of 5 × 10 cells / mL was added to a 96-well plate, and 100 μL was added to each well (about 5 × 10 cells per well). 3), and then returned to the cell culture incubator (37°C, 5% CO2, relative humidity 90%) for 24 hours. When the cells grow to a density of 80-90%, wash the cells with sterile PBS solution and add 100 μL of the above-prepared DMEM complete medium to continue culturing the cells. DMEM without extract was used as a negative control group. After 24 hours of culture, discard the culture medium and hydrogel, wash the cells again with sterile PBS, add CCK-8 solution (110 μL) diluted with culture medium 10:1, and return to the incubator incubated for 1-1.5 hours in the dark. Finally, measure the absorbance value A at the detection wavelength of 450nm, and calculate the cell survival rate by the following formula.

[0110]

[0111] A sample is the absorbance value of cells cultured with sample culture medium; A blank is the absorbance value of complete culture medium solution with 10% CCK-8 added; A control is the absorbance value of negative control group.

[0112] 10. Hemolysis test:

[0113] 40 μL of red blood cells were drawn into a 15 mL centrifuge tube, and 2 mL of deionized water was added to prepare a 2% (v / v) red blood cell suspension as a positive control; 1 mL of the previously diluted 4% red blood cell suspension was drawn into a 15 mL centrifuge tube, and 1 mL of PBS buffer was added to dilute it into a 2% red blood cell suspension as a negative control. After washing the hydrogel contact lenses of different groups, they were cut into the same size (r = 1.5 cm) and placed in 15 mL centrifuge tubes, and 1 mL of PBS was added. After shaking, 1 mL of 4% red blood cell suspension was drawn into each tube, and each sample was diluted into a 2% red blood cell suspension; the control group and the sample group were placed in a 37°C water bath and incubated for 3 hours at 4000 rpm·min -1 , centrifuged for 5 min, collected the supernatant, measured the absorbance of different groups at 540 nm using an ultraviolet spectrophotometer, and calculated the hemolysis rate using the following formula: DS is the absorbance of the experimental group, Dn is the absorbance of the negative control, and Dw is the absorbance of the positive control.

[0114]

[0115] 11. Eye irritation test:

[0116] The contact lenses of the Example Group that have been swollen in the liquid were cut to a size similar to the rat eyeball (R=0.8 mm) using a circular puncher, and then sterilized by ultraviolet light and worn on the healthy eyeball of the rat. The lenses were taken out after wearing for 8 hours every day, and the eyeball condition of the rat was recorded immediately. This process was repeated for three consecutive days, and the process was recorded as the eye irritation observation result.

[0117] Experimental results:

[0118] Table 2 Drug loading results of each example group

[0119]

[0120] As shown in Table 2, with the increase of EGCG drug loading concentration, the drug loading rate of the contact lens prepared in each embodiment gradually increased. Different drug loading concentrations may bring different cross-linking densities, resulting in different drug loading amounts.

[0121] like Figure 1 As shown, the hydrogel contact lenses of Examples 1-5 form a stable physical cross-linked network through hydrogen bonding and cation-π interactions. -1 The characteristic peak of -OH stretching vibration is shown at 1689cm -1 and 1613cm -1 The characteristic peak of C=O stretching vibration of EGCG indicates that EGCG is rich in hydroxyl groups. With the addition of obfEGCG, the peaks of Examples 2, 3, 4 and 5 become broader, showing a peak blue shift, up to 3394 cm -1 , and compared with Example 1, its peak signal intensity is enhanced, which indicates the formation of hydrogen bonds in the hydrogel network; at the same time, the peak signal intensity of Example 1 at 1610 cm -1 and 740cm -1 The characteristic peaks appear at the left and right sides, indicating the presence of benzene ring C=C and benzene ring CH; In addition, in each group of examples, the -C=O vibration of EGCG from 1689cm -1 The shift to higher wavenumbers can be attributed to the interaction between -C=O and hydrogen donors, which further proves the loading of EGCG monomer. -1 The -CH bonds attributable to the quaternized methyl groups in QCS shift to lower wavenumbers, indicating the presence of hydrogen bonding and cation-π interactions, confirming the loading of QCS.

[0122] like Figure 2 As shown, the water content of the hydrogel contact lenses of Examples 1-5 is greater than 40%, which meets the requirements of the national standard (GB11417), proving that the hydrogel contact lenses of Examples 1-5 have good water content.

[0123] like Figure 3 As shown, the transmittance of the hydrogels in Examples 1-5 in the visible light wavelength range is greater than 90%, which proves that the hydrogel contact lenses in Examples 1-5 have excellent light transmittance.

[0124] like Figure 4As shown, in the hydrogel contact lenses of Examples 1-5, after physical cross-linking with the traditional Chinese medicine monomers, their mechanical properties are significantly improved, and they have good tensile strength and elongation at break, thereby ensuring the durability and reliability of the contact lenses.

[0125] like Figure 5 As shown, the hydrogel contact lenses of Examples 2-5 have a drug sustained release effect and can continuously release drugs within 60 hours.

[0126] like Figure 6 As shown, the hydrogel contact lenses of Examples 1-5 were tested by scavenging DPPH· and ABTS· + The free radical scavenging ability of the hydrogel was evaluated experimentally, and the antioxidant capacity of the drug-containing hydrogel contact lens was confirmed. As the drug concentration increased, the antioxidant effect of the contact lens gradually increased.

[0127] like Figure 7 As shown, the hydrogel contact lenses of Examples 1-5 were tested by plate count method, which proved that each example had good antibacterial ability against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli).

[0128] like Figure 8 As shown, the hydrogel contact lens of the preferred embodiment 3 was subjected to in vivo efficacy study. Compared with the positive drug levofloxacin eye drops, the corneal tissue treated with the contact lens of the embodiment recovered rapidly, showing a more excellent therapeutic effect.

[0129] like Fig. 9 As shown, after the hydrogel contact lens of Example 3 was used to treat the animal model, the corneal tissue was tested for immunofluorescence, among which IL-6, IL-1β and TNF-α were representative inflammatory factors of infection-related inflammatory reactions. Compared with the obvious fluorescence expression of each inflammatory factor in other groups, there was almost no expression of inflammatory factors in the Example group, indicating that the hydrogel contact lens has a significant anti-inflammatory effect in the treatment of bacterial keratitis.

[0130] like Fig.10 As shown, the relative average fluorescence intensity of IL-6, IL-1β and TNF-α in each group in immunofluorescence was further semi-quantitatively analyzed. The inflammatory fluorescence intensity after treatment in Example 3 group and other groups was significantly different, further proving its excellent anti-inflammatory effect.

[0131] like Fig.11 As shown, the cell survival rates of the hydrogel contact lenses of Examples 1-5 were all greater than 80% through cytotoxicity assay, demonstrating that the material has good cell compatibility.

[0132] like Fig.12As shown, the hemolysis rates of the hydrogel contact lenses of Examples 1-5 were all lower than 5% through hemolysis assay, which proves that the material has good blood compatibility.

[0133] like Fig.13 This is a diagram showing the effect of the hydrogel contact lens on eye irritation in Example 2. In the continuous observation, there was no significant difference in the eyeballs of rats before and after wearing the contact lens. The eyeball structure was intact, the corneal substance was clear and transparent without turbidity, and the conjunctival blood vessels were clearly visible without obvious congestion. This shows that the contact lens was non-irritating to the rat eyeballs in the short term, did not cause any acute adverse eye reactions, and had good biological safety.

[0134] The above experimental results show that the drug-release multifunctional hydrogel corneal contact lens of each embodiment of the present invention has an ideal water content, excellent light transmittance and excellent mechanical strength, and can achieve drug sustained release. It has significant biological activity in anti-oxidation, antibacterial and anti-inflammatory aspects, especially in the treatment of bacterial keratitis, compared with the positive drug levofloxacin eye drops, the contact lens shows a more excellent therapeutic effect. In addition, the biosafety of the material has also been consistently confirmed by in vitro and in vivo studies, with good biocompatibility and safety, and is a potential new ophthalmic drug delivery system.

[0135] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a fast photocrosslinked drug sustained-release multifunctional hydrogel corneal contact lens, characterized in that: The preparation method comprises the following steps: (1) adding quaternized chitosan, acrylate monomers, and methacrylic acid to water in proportion, and using ultrasound and stirring to completely dissolve the quaternized chitosan; then adding a crosslinking agent and an initiator in sequence, and using ultrasound and stirring to completely dissolve the initiator to form a reaction mixture; (2) transferring the reaction mixture into a mold, performing a UV-light free radical polymerization reaction, and after the reaction is completed, removing the hydrogel from the mold and washing it, and freeze-drying the washed hydrogel to obtain a freeze-dried hydrogel; (3) Immersing the freeze-dried hydrogel in a drug monomer solution until the hydrogel is completely swollen to obtain a drug sustained-release multifunctional hydrogel corneal contact lens.

2. The method according to claim 1, characterized in that: The contents of the components in the reaction mixture in step (1) are: 30 vol% to 80 vol% of acrylate monomers, 0.6 vol% to 2 vol% of methacrylic acid, 0.001 to 3 g / L of quaternized chitosan, 0.5 vol% to 1.6 vol% of cross-linking agent, 0.01 to 1.5 g / L of initiator, and the balance is water.

3. The method according to claim 1, characterized in that The concentration of the drug monomer solution in step (3) is 0.01 to 10 g / L.

4. The method according to claim 1 or 2, characterized in that: The acrylic acid ester monomer is hydroxyethyl methacrylate or glyceryl methacrylate.

5. The method according to claim 1 or 2, characterized in that: The drug monomer is any one or at least two of epigallocatechin gallate, epicatechin, epigallocatechin, chlorogenic acid, gallic acid, salidroside and salvianolic acid B.

6. The method according to claim 1 or 2, characterized in that: The crosslinking agent is ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol diacrylate, polyethylene glycol dimethacrylate or dicyclopentenyl acrylate.

7. The method according to claim 1 or 2, characterized in that: The initiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone I2959 or 2-hydroxy-2-methyl-1-phenyl-1-propanone D1173.

8. The method according to claim 1, characterized in that In step (2), the wavelength of the ultraviolet light for free radical polymerization is 300-400 nm, and the intensity of the light is 10-1500 mW / cm 2 , polymerization time 15-40min; the demoulding temperature is 70-80°C, and after demoulding, the hydrogel is washed in pure water for 3-7d.

9. The method according to claim 1, characterized in that: In step (3), the freeze-dried hydrogel is immersed in the drug monomer solution on a shaker in the dark, the immersion temperature is 15-40° C., the rotation speed is 100 rpm, and the immersion time is 24-72 h.

10. A fast photo-crosslinked drug sustained-release multifunctional hydrogel contact lens prepared by the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Chitosan hydrogel derivatives as a coating agent with broad spectrum of antimicrobial activities

    CN102712700A

  • Preparation method of antibacterial corneal contact lenses based on crosslinking copolymerization

    CN104193890A

  • Drug-loaded contact lens with antibacterial effect and preparation method thereof

    CN112500528A

  • Drug-loaded anti-adhesion contact lens hydrogel material and preparation method thereof

    CN112795030A

  • Multifunctional pHEMA-based corneal contact lens hydrogel material as well as preparation method and application thereof

    CN113248656A

Cited By

  • High-moisture-retention antibacterial silicone hydrogel contact lens material and preparation method thereof

    CN120737532A

  • A high-moisture and antibacterial silicone hydrogel contact lens material and a preparation method thereof

    CN120737532B